Peroxynitrite Mediates Testosterone-Induced Vasodilation of Microvascular Resistance Vessels - Puttabyatappa, Yashoda; Stallone, John N.; Ergul, Adviye; El-Remessy, Azza B.; Kumar, Sanjiv; Black, Stephen; Johnson, Maribeth; Owen, Mary P.; White, Richard E. (The Journal of pharmacology and experimental therapeutics, 2013)
Our knowledge of how androgens influence the cardiovascular system is far from complete, and this lack of understanding is especially true of how androgens affect resistance vessels. Our aim was to identify the signaling mechanisms stimulated by testosterone (TES) in microvascular arteries and to understand how these mechanisms mediate TES-induced vasodilation. Mesenteric microvessels were isolated from male Sprague-Dawley rats. Tension studies demonstrated a rapid, concentration-dependent, vasodilatory response to TES that did not involve protein synthesis or aromatization to 17β-estradiol. Dichlorofluorescein fluorescence and nitrotyrosine immunoblot experiments indicated that TES stimulated peroxynitrite formation in microvessels, and functional studies demonstrated that TES-induced vasodilation was inhibited by scavenging peroxynitrite. As predicted, TES enhanced the production of both peroxynitrite precursors (i.e., superoxide and nitic oxide), and xanthine oxidase was identified as the likely source of TES-stimulated superoxide production. Functional and biochemical studies indicated that TES signaling involved activity of the phosphoinositide 3 (PI3) kinase-protein kinase B (Akt) cascade initiated by activation of the androgen receptor and culminated in enhanced production of cGMP and microvascular vasodilation. These findings, derived from a variety of analytical and functional approaches, provide evidence for a novel nongenomic signaling mechanism for androgen action in the microvasculature: TES-stimulated vasodilation mediated primarily by peroxynitrite formed from xanthine oxidase-generated superoxide and NO. This response was associated with activation of the PI3 kinase-Akt signaling cascade initiated by activation of the androgen receptor. We propose this mechanism could account for TES-stimulated cGMP production in microvessels and, ultimately, vasodilation.